Short carbon fiber reinforced carbon ceramic brake disc and preparation method thereof

CN122916706APending Publication Date: 2026-10-16ANHUI AOFU AUTO PARTS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611143366.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

虽然制备方法得到了简化,但强度低,并且碳纤维易被熔融硅腐蚀

Benefits of technology

(1)本发明的短切碳纤维增强碳陶制动盘的制备方法,在短切碳纤维表面沉积保护层,能够有效隔绝后续高温真空熔融渗硅过程中熔融硅对碳纤维的腐蚀,使碳纤维单丝能够完整保留,充分发挥其增强作用;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916706A_ABST
    Figure CN122916706A_ABST
Patent Text Reader

Abstract

The application relates to the technical field of brake disc manufacturing, in particular to a chopped carbon fiber reinforced carbon ceramic brake disc and a preparation method thereof. The method comprises the following steps: depositing a protective layer on the surface of chopped carbon fibers, mixing the chopped carbon fibers with carbon resin and inorganic powder to obtain a mixture, and performing mold hot forming, high-temperature carbonization and high-temperature vacuum melting silicon infiltration on the mixture to obtain a brake disc. The protective layer comprises at least one coating layer, and the material of each coating layer is one of C, SiC, BN, SiBCN, SiBN, Si3N4 and TiB2. The method can effectively isolate the corrosion of molten silicon on the carbon fibers in the subsequent high-temperature vacuum melting silicon infiltration process, so that the carbon fiber monofilament can be completely reserved and fully play a reinforcing role. The brake disc has the advantages of light weight, high strength, high wear resistance, high thermal stability and low noise, and is suitable for various braking scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of brake disc manufacturing technology, and more specifically, to a short-cut carbon fiber reinforced carbon ceramic brake disc and its preparation method. Background Technology

[0002] Currently, most brake discs on the market are metal discs. During braking, friction generates heat, causing the brake disc temperature to rise rapidly, thus reducing the coefficient of friction, a phenomenon often referred to as thermal degradation, leading to brake instability. Metal discs have a lower heat resistance; when the temperature exceeds 450℃, they will deform, resulting in noise during braking and decreased stability. Metal discs also have lower hardness, leading to greater frictional wear and a shorter lifespan. Furthermore, metal discs have a high specific gravity (~8g / cm³). 3 Therefore, it consumes a lot of energy.

[0003] To address the shortcomings of metal brake discs, carbon fiber reinforced ceramic matrix composite brake discs, commonly known as carbon-ceramic discs, have been developed both domestically and internationally. Compared to metal discs, carbon-ceramic discs have a lower density (1.8 g / cm³). 3 ~2.5g / cm 3 It has high heat resistance (>1000℃), stable friction performance (no thermal degradation), low friction loss, and a lifespan far longer than that of metal discs.

[0004] Currently, there are two types of carbon ceramic discs: long-fiber carbon ceramic discs and short-fiber carbon ceramic discs. These two types of carbon ceramic discs use different manufacturing technologies, resulting in significant differences in performance and cost.

[0005] The long-fiber carbon ceramic disc is made by cross-laminating unidirectional carbon fiber cloth and non-woven carbon fiber cloth, and then using CVI (chemical vapor infiltration) to deposit pyrolytic carbon, which densifies the preform to a set density, resulting in a porous C / C composite material. This method can protect the carbon fibers from corrosion and loss of reinforcing effect during the subsequent melt-infiltrating process.

[0006] While long-fiber carbon ceramic discs offer high strength and toughness, their production efficiency is low (tens of hours), resulting in high costs. Furthermore, due to the high residual carbon content (~40%) and low silicon carbide content (20%~30%), the products exhibit poor thermal conductivity, leading to slow frictional heat dissipation, high surface temperatures, carbon fiber oxidation, and high wear. Additionally, ventilation holes cannot be directly fabricated in long-fiber carbon ceramic discs; they must be formed through machining, further increasing production costs. Moreover, only simple ventilation channels can be created, resulting in poor ventilation and cooling effects.

[0007] Short-fiber carbon ceramic discs are typically made by combining carbon fibers with carbon resin, then pressing the mixture into a brake disc in one step using high-temperature graphitization and molding techniques. Although the manufacturing method is simplified, the strength is low, and the carbon fibers are easily corroded by molten silicon. Summary of the Invention

[0008] The technical problem to be solved by the present invention is to provide a short-cut carbon fiber reinforced carbon ceramic brake disc and its preparation method.

[0009] The technical solution of the present invention to solve the above-mentioned technical problems is as follows: This invention provides a method for preparing a short-cut carbon fiber reinforced carbon ceramic brake disc. A protective layer is deposited on the surface of short-cut carbon fibers, which are then mixed with carbon resin and inorganic powder to obtain a mixture. The mixture is subjected to compression molding, high-temperature carbonization, and high-temperature vacuum melt infiltration to obtain the brake disc. The protective layer includes at least one coating layer, and each coating layer is made of one of the following materials: C, SiC, BN, SiBCN, SiBN, Si3N4, and TiB2.

[0010] Based on the above technical solution, the present invention can be further improved as follows.

[0011] Furthermore, the total thickness of the protective layer is 0.1µm-1.5µm; the length of the chopped carbon fiber is 1mm-20mm, and the specification is 1k-24k.

[0012] Furthermore, the protective layer includes a Si3N4 coating and a pyrolytic carbon coating; the protective layer is prepared by first depositing the Si3N4 coating on the surface of the short-cut carbon fiber using chemical vapor deposition, and then depositing the pyrolytic carbon coating on the outside of the Si3N4 coating.

[0013] Furthermore, the temperature of the chemical vapor deposition method is 850℃~1050℃, and the heating rate is 1℃ / min~10℃ / min.

[0014] Furthermore, in the mixture, the volume percentage of the chopped carbon fibers is 15%-40%, the volume percentage of the carbon resin is 45%-70%, and the volume percentage of the inorganic powder is 1%-10%.

[0015] Furthermore, the carbon resin is at least one of phenolic resin, solid furan resin, and asphalt; the inorganic powder is at least one of graphite, carbon, Si3N4, TiB2, and SiC, and the particle size of the inorganic powder is 0.2µm-10µm.

[0016] Furthermore, the temperature of the compression molding thermoforming is 100℃-260℃, the pressure is 0.8MPa-3.0MPa, and the holding time is 1 hour-10 hours.

[0017] Furthermore, the high-temperature carbonization is carried out in an inert atmosphere, with a heating rate of 5℃ / hour to 15℃ / hour, a target temperature of 850℃ to 1100℃, and a holding time of 0.5 hours to 3 hours.

[0018] Furthermore, the high-temperature vacuum melt silicon infiltration method involves embedding the brake disc intermediate obtained by the high-temperature carbonization in silicon particles, heating it to 1600°C at a heating rate of 300°C / hour under a vacuum environment of 1Pa-300Pa, holding it at that temperature for 0.2 hours to 3 hours, and then cooling it to obtain the carbon-ceramic brake disc.

[0019] The present invention also provides a short-cut carbon fiber reinforced carbon ceramic brake disc, which is obtained by the preparation method described above.

[0020] The beneficial effects of this invention are as follows: (1) The method for preparing the short carbon fiber reinforced carbon ceramic brake disc of the present invention deposits a protective layer on the surface of the short carbon fiber, which can effectively isolate the corrosion of the carbon fiber by the molten silicon during the subsequent high temperature vacuum melting and silicon infiltration process, so that the carbon fiber monofilament can be completely preserved and give full play to its reinforcing effect. (2) The method for preparing the short-cut carbon fiber reinforced carbon ceramic brake disc of the present invention allows the short-cut carbon fiber to be uniformly dispersed in the matrix, effectively improving the strength of the brake disc; (3) The method for preparing the short-cut carbon fiber reinforced carbon ceramic brake disc of the present invention can press out complex-shaped ventilation channels that conform to fluid dynamics in one go, without the need for subsequent machining, which further simplifies the process and reduces costs; (4) The short-cut carbon fiber reinforced carbon ceramic brake disc of the present invention has the comprehensive advantages of lightweight, high strength, high wear resistance, high thermal stability and low noise, and is suitable for various braking scenarios such as passenger cars, heavy trucks, trains and airplanes. Attached Figure Description

[0021] Figure 1 This is a schematic diagram showing the phase distribution in the carbon ceramic dish of Embodiment 1 of the present invention; Figure 2 This is a schematic diagram showing the phase distribution in the carbon ceramic dish of Comparative Example 1 of the present invention. Detailed Implementation

[0022] The principles and features of the present invention are described below. The examples given are only for explaining the present invention and are not intended to limit the scope of the present invention.

[0023] The present invention discloses a method for preparing a short-cut carbon fiber reinforced carbon ceramic brake disc, wherein a protective layer is deposited on the surface of short-cut carbon fibers, and then mixed with carbon resin and inorganic powder to obtain a mixture; the mixture is subjected to compression molding, high-temperature carbonization, and high-temperature vacuum melt infiltration to obtain a brake disc; the protective layer includes at least one coating layer, and each coating layer is made of one of C, SiC, BN, SiBCN, SiBN, Si3N4, and TiB2.

[0024] The method for preparing the chopped carbon fiber reinforced carbon ceramic brake disc of the present invention involves directly depositing a protective layer on the surface of each chopped carbon fiber filament, thereby ensuring uniform dispersion of the chopped carbon fiber in the composite material. This avoids the uneven dispersion problem caused by the carbon fiber being bundled by a graphitized carbon layer in traditional chopped carbon ceramic discs, significantly improving the reinforcement and toughening effect. The protective layer material of the present invention can effectively isolate the carbon fiber from corrosion by molten silicon during the subsequent high-temperature vacuum melting and silicon infiltration process, allowing the carbon fiber filaments to be completely preserved and uniformly distributed in the matrix, fully exerting their reinforcing effect. At the same time, the protective layer material can be flexibly selected according to different performance requirements.

[0025] In the preparation method of the present invention, the carbon fiber monofilament level protection makes the preform after molding have good structural stability during carbonization and silicon infiltration. Combined with the molding technology, complex-shaped ventilation channels that conform to hydrodynamics can be pressed in one go without subsequent machining, which further simplifies the process and reduces costs.

[0026] Preferably, the total thickness of the protective layer of the present invention is 0.1µm-1.5µm, and most preferably 0.2µm-1.0µm. Although this thickness is only at the submicron level, it can effectively achieve the protective function. Unlike traditional processes, it does not rely on a large amount of pyrolytic carbon or a thick graphitized carbon layer to coat the fibers. Therefore, the final product does not contain residual carbon, has a high silicon carbide content, significantly improves the thermal conductivity and oxidation resistance of the brake disc, makes the friction performance more stable, and significantly reduces carbon fiber oxidation and wear during service.

[0027] Preferably, the length of the chopped carbon fiber is 1mm-20mm, and the specification is 1k-24k; where 1k represents 1000 carbon fiber monofilaments. The specifications of the chopped carbon fiber are 1k, 3k, 6k, 12k or 24k; the length of the chopped carbon fiber is preferably 5mm-12mm.

[0028] Preferably, the grade of short-cut carbon fiber is T300, T700 or T800; the best is T700; T700 short-cut carbon fiber has both good performance and low cost.

[0029] In one embodiment of the present invention, the protective layer includes a Si3N4 coating and a pyrolytic carbon coating (Si3N4-C composite coating); the Si3N4 coating has good high-temperature stability and chemical inertness, while the pyrolytic carbon coating has good compatibility with the carbon fiber matrix, and the multi-layer composite coating can meet different functional requirements.

[0030] The protective layer is prepared by first depositing the Si3N4 coating on the surface of the short-cut carbon fiber using chemical vapor deposition (CVD), and then depositing a pyrolytic carbon coating on the outside of the Si3N4 coating. Compared with the traditional high-temperature graphitization coating process, the CVD technology for depositing the protective layer is simpler, avoids the lengthy graphitization process and the complex carbon layer coating process, shortens the preparation cycle, and reduces production costs.

[0031] Preferably, the temperature for chemical vapor deposition is 850℃~1050℃ and the heating rate is 1℃ / min~10℃ / min.

[0032] In the preparation method of the present invention, the volume percentage of short-cut carbon fibers in the mixture is 15%-40%, the volume percentage of carbon resin is 45%-70%, and the volume percentage of inorganic powder is 1%-10%.

[0033] Within the aforementioned volume percentage range, chopped carbon fibers can be evenly distributed in the matrix to form an effective reinforcing network, ensuring that the brake disc obtains sufficient reinforcement and toughening effects. When the content is too low, the reinforcement effect is insufficient, resulting in low strength. When the content is too high, the fibers are difficult to disperse evenly and molding is difficult.

[0034] Within the aforementioned volume percentage range, carbon resin can provide sufficient bonding and flow properties during the molding process, enabling the mixture to be fully densified and shaped into the desired brake disc blank in subsequent steps. At the same time, the carbon matrix formed after resin carbonization provides a carbon source for the subsequent melt infiltration reaction to generate SiC. This content range can ensure both the quality of the blank forming and the full progress of the infiltration reaction.

[0035] Within the aforementioned volume percentage range, inorganic powders, as fillers, can adjust the rheological properties of the mixture, improve molding properties, and participate in or promote reactions at high temperatures, thereby enhancing the frictional performance and wear resistance of the brake disc. However, excessively high inorganic powder content can dilute the reinforcing effect of carbon fibers and increase brittleness.

[0036] Preferably, the volume percentage of chopped carbon fibers in the mixture is 20%-30%, the volume percentage of carbon resin is 55%-65%, and the volume percentage of inorganic powder is 3%-8%.

[0037] Preferably, the carbon resin is at least one of phenolic resin, solid furan resin, and pitch, and all are in powder form; the inorganic powder is at least one of graphite, carbon, Si3N4, TiB2, and SiC, and the particle size of the inorganic powder is 0.2µm-10µm.

[0038] The method for preparing the short-cut carbon fiber reinforced carbon ceramic brake disc of the present invention specifically includes the following steps: S1. Cut the carbon fiber into short carbon fibers of a fixed length.

[0039] S2. A protective layer is prepared on the surface of each carbon fiber using CVD technology.

[0040] S3. The short-cut carbon fibers with protective layer are mixed with carbon resin and inorganic powder to obtain a mixture.

[0041] S4. The mixture is loaded into a metal mold and pressed in one step using compression molding technology. Then it is heated and shaped under pressure to obtain the brake disc blank.

[0042] In this step, the ventilation channels in the brake disc are simultaneously formed during molding.

[0043] Preferably, the temperature for compression molding in this step is 100℃-260℃, with an optimal temperature of 130℃~160℃; the pressure is 0.8MPa-3.0MPa, with an optimal pressure of 1.0MPa~2.0MPa; and the holding time is 1 hour-10 hours, with an optimal holding time of 3 hours~6 hours.

[0044] S5. The brake disc blank is heated to a suitable temperature under an inert atmosphere for pyrolysis, converting the carbon resin into carbon and achieving high-temperature carbonization.

[0045] Preferably, the inert atmosphere in this step is nitrogen.

[0046] Preferably, the heating rate in this step is 5℃ / hour to 15℃ / hour, and the optimal rate is 5℃ / hour to 8℃ / hour; slow heating can effectively increase the residual carbon content of the carbon resin and reduce the deformation rate of the brake disc.

[0047] Preferably, the target temperature is 850℃-1100℃, and the optimal temperature is 950℃~1050℃; the heat preservation time is 0.5 hours-3 hours, and the optimal temperature is 1 hour.

[0048] S6. High-temperature vacuum melting and silicon infiltration is carried out and kept at a temperature so that silicon reacts with carbon in the matrix to form SiC. Finally, a small amount of unreacted residual silicon fills the remaining pores to achieve densification of the brake disc.

[0049] Specifically, the high-temperature vacuum melting silicon infiltration method in this step involves embedding the brake disc intermediate obtained by high-temperature carbonization in silicon particles, heating it to 1600°C at a heating rate of 300°C / hour under a vacuum environment of 1Pa-300Pa, holding it at that temperature for 0.2 hours to 3 hours, and then cooling it to obtain a carbon ceramic brake disc.

[0050] Preferably, the temperature is 1600℃~1700℃, the vacuum degree is 20Pa~50Pa, and the holding time is 0.5 hours~1.0 hours.

[0051] The above-mentioned preparation method of the present invention produces a brake disc composite material that contains no residual carbon, has a SiC content of more than 70%, and exhibits high thermal conductivity and oxidation resistance. The method also has the advantages of simple process, high efficiency, and low cost.

[0052] The short-cut carbon fiber reinforced carbon ceramic brake disc of the present invention is obtained by the above-described preparation method.

[0053] The short-cut carbon fiber reinforced carbon ceramic brake disc of the present invention has a bending strength greater than 90MPa and an elongation at break greater than 0.2%, which is superior to the traditional short-cut fiber carbon ceramic disc (40MPa~80MPa) and close to or even reaches the level of long fiber carbon ceramic disc (90MPa~125MPa).

[0054] Meanwhile, the final brake disc density is greater than 2.4 g / cm³. 3 With a porosity of less than 3% and a friction coefficient greater than 0.5 at room temperature, it combines the advantages of lightweight, high strength, high wear resistance, high thermal stability and low noise, making it suitable for various braking scenarios such as passenger cars, heavy trucks, trains and airplanes.

[0055] The present invention will be specifically described below through specific embodiments: Example 1 The preparation steps in this embodiment are as follows: (1) Short-cut high-strength carbon fiber is used as the reinforcement. The bundle specification is 24k, the average fiber diameter is 7.3µm, the tensile strength is 5.2GPa, the elastic modulus is 235GPa, and the length is 12mm.

[0056] (2) A Si3N4 coating with a thickness of 0.8µm was first prepared on the fiber surface using CVD technology, and then a pyrolytic carbon coating with a thickness of 0.2µm was prepared.

[0057] In this embodiment, the CVD temperature is 850°C and the heating rate is 5°C / minute.

[0058] (3) The coated carbon fiber is mixed with phenolic resin powder and TiB2 powder. The prepared mixture contains 20% carbon fiber, 8% TiB2 and 72% phenolic resin.

[0059] The phenolic resin powder includes phenolic resin and curing agent hexamethylenetetramine, with hexamethylenetetramine accounting for 8% of the phenolic resin by mass, and the TiB2 powder having a particle size of 2µm.

[0060] (4) Carbon ceramic disc green blanks were prepared by molding method, with molding temperature of 150℃, holding time of 5 hours, and pressure of 1.6MPa.

[0061] (5) Pyrolysis is carried out under flowing nitrogen gas, with a heating rate of 5℃ / hour to 600℃, then 100℃ / hour to 1000℃, and the temperature is maintained for 1 hour before cooling down in the furnace to obtain a porous composite material brake disc intermediate.

[0062] (6) The intermediate body of the brake disc is embedded in Si particles (average particle size 2.3 mm), heated to 1600 °C at a rate of 300 °C / hour under a vacuum of 20 Pa, and cooled down with the furnace after holding for 1 hour to obtain a carbon ceramic brake disc.

[0063] The brake disc obtained in this embodiment has the following chemical composition: 21% carbon fiber, 67% SiC, 9% TiB2, and 3% Si. The density of the brake disc is 2.45 g / cm³. 3 It has a porosity of 2.6%, a flexural strength of 93 MPa, an elongation at break of 0.32%, and a coefficient of friction of 0.55 at room temperature.

[0064] Example 2 The preparation steps in this embodiment are as follows: (1) Short-cut high-strength carbon fiber is used as the reinforcement. The bundle specification is 12k, the average fiber diameter is 7.0µm, the tensile strength is 4.9GPa, the elastic modulus is 230GPa, and the length is 8mm.

[0065] (2) A 0.5µm thick BN coating was first prepared on the fiber surface using CVD technology, and then a 0.3µm thick SiC coating was prepared.

[0066] In this embodiment, the CVD temperature is 1050℃ and the heating rate is 10℃ / minute.

[0067] (3) The coated carbon fiber is mixed with solid furan resin powder and Si3N4 powder (particle size 5µm). The prepared mixture contains 30% carbon fiber, 5% Si3N4 and 65% furan resin.

[0068] (4) Carbon ceramic disc green blanks were prepared by molding method, with molding temperature of 160℃, holding time of 6 hours, and pressure of 2.0MPa.

[0069] (5) Pyrolysis was carried out under flowing nitrogen gas, with a heating rate of 8℃ / hour to 600℃, then 80℃ / hour to 1050℃, and the temperature was maintained for 1.5 hours before cooling down in the furnace to obtain a porous composite material brake disc intermediate. (6) The intermediate body of the brake disc is embedded in Si particles (average particle size 2.5 mm), heated to 1650 °C at a rate of 250 °C / hour under a vacuum of 30 Pa, held for 0.5 hours and then cooled down with the furnace to obtain a carbon ceramic brake disc.

[0070] The brake disc in this embodiment has a chemical composition of 30% carbon fiber, 62% SiC, 6% Si3N4, and 2% Si, with a density of 2.46 g / cm³. 3 It has a porosity of 2.9%, a flexural strength of 102 MPa, an elongation at break of 0.35%, and a coefficient of friction of 0.61 at room temperature.

[0071] Example 3 The preparation steps in this embodiment are as follows: (1) Short-cut high-strength carbon fiber is used as the reinforcement. The bundle specification is 6k, the average fiber diameter is 6.8µm, the tensile strength is 5.0GPa, the elastic modulus is 240GPa, and the length is 5mm.

[0072] (2) A 1.0µm thick SiBCN coating was prepared on the fiber surface using CVD technology.

[0073] In this embodiment, the CVD temperature is 1000℃ and the heating rate is 10℃ / minute.

[0074] (3) The coated carbon fiber is mixed with furan resin powder, pitch powder and graphite powder (particle size 3µm) to prepare a mixture with carbon fiber content of 15%, graphite content of 10%, furan resin content of 50% and pitch content of 25%.

[0075] (4) Carbon ceramic disc green blanks were prepared by molding method, with molding temperature of 130℃, holding time of 3 hours, and pressure of 1.0MPa.

[0076] (5) Pyrolysis was carried out under flowing nitrogen gas, with a heating rate of 5℃ / hour to 600℃, then 120℃ / hour to 950℃, and the temperature was maintained for 0.5 hours before cooling down with the furnace to obtain a porous composite material brake disc intermediate. (6) The intermediate body of the brake disc is embedded in Si particles (average particle size 2.0 mm), heated to 1700 °C at a rate of 350 °C / hour under a vacuum of 50 Pa, and held for 2 hours before being cooled down in the furnace to obtain a carbon ceramic brake disc.

[0077] The brake disc in this embodiment has a chemical composition of 16% carbon fiber, 80% SiC, and 4% Si, with a density of 2.48 g / cm³. 3 It has a porosity of 2.2%, a flexural strength of 82 MPa, an elongation at break of 0.17%, and a coefficient of friction of 0.52 at room temperature.

[0078] Comparative Example 1 The short-cut carbon fibers used in this comparative example have no protective layer, and the carbon fibers are directly corroded by molten silicon.

[0079] This comparative example uses the same short-cut high-strength carbon fibers as in Example 1, but without the CVD-deposited protective layer, and is directly mixed with phenolic resin powder and TiB2 powder. Other preparation steps and parameters are exactly the same as in Example 1.

[0080] In the brake disc obtained in this comparative example, almost all the carbon fiber was corroded by molten silicon, leaving only a small amount of residual carbon fiber fragments. The chemical composition was: 2% residual carbon fiber, 79% SiC, 9% TiB2, and 10% Si. The brake disc density was 2.9 g / cm³. 3 The porosity is 3.7%, the flexural strength is 95MPa, the elongation at break is 0.07%, and the coefficient of friction at room temperature is 0.38. Due to the loss of the carbon fiber reinforcement, the brake disc is brittle and cannot meet the usage requirements.

[0081] Comparative Example 2 This comparative example was prepared using a traditional graphitized carbon layer coating process.

[0082] This comparative example uses the same short-cut high-strength carbon fibers as in Example 1. The carbon fibers are composited with phenolic resin and then carbonized to form a C / C composite material. After multiple resin impregnations and carbonizations, a low-porosity C / C composite material is obtained. Then, it is graphitized at 2000℃ to form carbon fiber bundles coated with a graphitized carbon layer. The graphitized C / C composite material is then processed into short-cut C / C bundles, approximately 12 mm in length, using a cutting and shredding machine.

[0083] The above-mentioned short-cut C / C bundles were mixed with phenolic resin powder and TiB2 powder, and the amount of each component and the preparation parameters were the same as in Example 1.

[0084] In this comparative example brake disc, carbon fibers are bundled and coated with graphitized carbon layers. The chemical composition is 20% carbon fiber, 63% SiC, 8% TiB2, 6% residual carbon, and 3% Si. The brake disc density is 2.38 g / cm³. 3 It has a porosity of 2.8%, a flexural strength of 62 MPa, an elongation at break of 0.24%, and a coefficient of friction of 0.65 at room temperature.

[0085] A comprehensive comparison of the above embodiments and comparative examples shows that all three embodiments achieve excellent performance, including single-filament protection of carbon fiber, no residual carbon, SiC content higher than 70% (including fillers), flexural strength greater than 90 MPa, and porosity lower than 3%. In contrast, the carbon fiber in Comparative Example 1 was almost entirely corroded by molten silicon, resulting in a brittle brake disc that cannot meet practical application requirements.

[0086] Meanwhile, Comparative Example 2, prepared using a traditional method, exhibited uneven carbon fiber distribution, resulting in poor performance. The underlying principles of both methods are analyzed in detail below: Figure 1This is a schematic diagram of the phase distribution in the carbon ceramic dish of Example 1. Red represents the protective coating on the carbon fiber surface, black circles represent carbon fibers, and gray represents SiC and residual silicon generated by the reaction. Figure 2 This is a schematic diagram of the phase distribution in the carbon ceramic dish of Comparative Example 2. Purple represents graphitized carbon in the short fiber bundles, black circles represent carbon fibers, and gray represents SiC and residual silicon generated in the reaction.

[0087] It can be seen that, Figure 2 In the short-cut carbon fiber ceramic disc, the carbon fibers are tightly coated with graphitized carbon, thus preventing contact with molten silicon. Because the graphitized carbon layer coating the carbon fibers is very thin, the residual carbon in the final ceramic disc is much lower than in long-fiber ceramic discs, significantly improving the disc's oxidation resistance and thermal conductivity. Figure 1 In this process, each carbon fiber monofilament is coated with a protective coating to protect it from corrosion by molten silicon. Ultimately, the carbon fiber monofilaments are evenly distributed in the SiC+ residual silicon matrix, which significantly improves its reinforcement and toughening effect, increases the SiC content of the brake disc and reduces the residual carbon content, thereby further improving its oxidation resistance and thermal conductivity.

[0088] The above embodiments and comparative examples fully demonstrate the criticality of the present invention in depositing a protective layer on short-cut carbon fibers.

[0089] Although embodiments of the present invention have been shown and described above, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Those skilled in the art can make changes, modifications, substitutions and variations to the above embodiments within the scope of the present invention.

Claims

1. A method for preparing a short-cut carbon fiber reinforced carbon ceramic brake disc, characterized in that, A protective layer is deposited on the surface of short-cut carbon fibers, which are then mixed with carbon resin and inorganic powder to obtain a mixture. The mixture is subjected to compression molding, high-temperature carbonization, and high-temperature vacuum melt silicon infiltration to obtain the brake disc. The protective layer includes at least one coating layer, and each coating layer is made of one of the following materials: C, SiC, BN, SiBCN, SiBN, Si3N4, and TiB2.

2. The method for preparing a short-cut carbon fiber reinforced carbon ceramic brake disc according to claim 1, characterized in that, The total thickness of the protective layer is 0.1µm-1.5µm; the length of the short-cut carbon fiber is 1mm-20mm, and the specification is 1k-24k.

3. The method for preparing a short-cut carbon fiber reinforced carbon ceramic brake disc according to claim 2, characterized in that, The protective layer includes a Si3N4 coating and a pyrolytic carbon coating. The protective layer is prepared by first depositing the Si3N4 coating on the surface of the short-cut carbon fibers using chemical vapor deposition, and then depositing the pyrolytic carbon coating on the outside of the Si3N4 coating.

4. The method for preparing a short-cut carbon fiber reinforced carbon ceramic brake disc according to claim 3, characterized in that, The temperature of the chemical vapor deposition method is 850℃~1050℃, and the heating rate is 1℃ / min~10℃ / min.

5. The method for preparing a short-cut carbon fiber reinforced carbon ceramic brake disc according to claim 1, characterized in that, In the mixture, the volume percentage of the short-cut carbon fibers is 15%-40%, the volume percentage of the carbon resin is 45%-70%, and the volume percentage of the inorganic powder is 1%-10%.

6. The method for preparing a short-cut carbon fiber reinforced carbon ceramic brake disc according to claim 5, characterized in that, The carbon resin is at least one of phenolic resin, solid furan resin, and asphalt; the inorganic powder is at least one of graphite, carbon, Si3N4, TiB2, and SiC, and the particle size of the inorganic powder is 0.2µm-10µm.

7. A method for preparing a short-cut carbon fiber reinforced carbon ceramic brake disc according to any one of claims 1-6, characterized in that, The temperature for the compression molding thermoforming is 100℃-260℃, the pressure is 0.8MPa-3.0MPa, and the holding time is 1 hour-10 hours.

8. A method for preparing a short-cut carbon fiber reinforced carbon ceramic brake disc according to any one of claims 1-6, characterized in that, The high-temperature carbonization is carried out in an inert atmosphere, with a heating rate of 5℃-15℃ / hour, a target temperature of 850℃-1100℃, and a holding time of 0.5 hours-3 hours.

9. A method for preparing a short-cut carbon fiber reinforced carbon ceramic brake disc according to any one of claims 1-6, characterized in that, The high-temperature vacuum melting silicon infiltration method involves embedding the brake disc intermediate obtained by the high-temperature carbonization in silicon particles, heating it to 1600°C at a heating rate of 300°C / hour under a vacuum environment of 1Pa-300Pa, holding it at that temperature for 0.2 hours to 3 hours, and then cooling it to obtain the carbon-ceramic brake disc.

10. A short-cut carbon fiber reinforced carbon ceramic brake disc, characterized in that, It is obtained by the preparation method described in any one of claims 1-9.